Associations between body weight perception and weight control behaviour in South Indian children: a cross-sectional study. Issue 3 (9th March 2013) - Swaminathan, Sumathi; Selvam, Sumithra; Pauline, Maria; Vaz, Mario
Abstract : Objective: To examine the patterns of weight loss behaviour and the association between weight loss attempts with actual weight status and children's and parental perceptions of weight status. Design: A cross-sectional study. Setting: Karnataka, South India. Participants: 1874 girls and boys aged 8–14 years from seven schools in Karnataka, South India. Main outcome measures: The association between weight loss attempts and sociodemographic factors, weight status and the child's or the parent's perception of weight status. Results: Approximately 73% of overweight and obese, 35% of normal weight and 22% of underweight children attempted to lose weight. Children of lower socioeconomic groups studying in schools in the local vernacular and overweight/obese children were more likely to attempt to lose weight (adjusted OR ie, AOR=1.57, 95% CI 1.11 to 2.25; AOR=4.38, 95% CI 2.64 to 7.28, respectively). Perception of weight status was associated with weight loss attempts. Thus, children who were of normal weight but perceived themselves to be overweight/obese were three times more likely to attempt weight loss compared with those who accurately perceived themselves as being of normal weight, while the odds of attempting weight loss were the highest for those who were overweight and perceived themselves to be so (AOR∼18). Conclusions: Children are likely to attempt weight loss in India irrespective of their weight status, age and gender. Children who were actually overweight as well as those who were perceived by themselves or by their parents to be overweight or obese were highly likely to try to lose weight. It is necessary to understand body weight perceptions in communities with a dual burden of being overweight and undernourished, if intervention programmes for either are to be successful.